Peningkatan Kesadaran Ibu Hamil untuk Mencegah Kejadian Preeklamsia di Posyandu Dahlia XI Wilayah Kerja Puskesmas Tanjungpura Kabupaten Karawang - Rifka Alindawati; Siti Sopiatun; Sri Maryati; Rochmawati Rochmawati (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Preeclampsia constitutes an obstetric complication with 5.3% prevalence in Indonesia, significantly contributing to maternal mortality rates. Cognitive deficiency among pregnant women regarding preeclampsia risk factors represents a fundamental determinant in primary preventive strategies. This research aimed to optimize awareness and comprehensive knowledge of gravidas concerning preeclampsia through implementation of structured health education programs. Research methodology employed participatory action research involving 13 gravida respondents at Posyandu Dahlia XI, Karawang Regency. Comprehensive educational interventions encompassed interactive counseling, applicative demonstrations, and educational media development. Pre-post test evaluation demonstrated significant escalation of optimal knowledge categories from 38.46% to 84.61% of respondents post-intervention. The program successfully generated behavioral transformation, establishment of sustainable peer support mechanisms, and formation of collective community awareness. Implementation of participatory health education proved effective in cognitive enhancement and gravida awareness toward preeclampsia preventive strategies, resulting in sustainable behavioral modification within maternal communities. This intervention model demonstrates significant potential for replication in similar healthcare settings